SNAP, WIC, Low-Income Families, Fruits & Vegetables and Food Security : An Investigation of Food Purchasing Behaviors II - Fogarty, Jared; Gilger, Nathan; Halverson, Emma; Miller, Ben; Perinchery, Rivin; Schneider, Kelly; Soborowicz, Levi; Stephani, Shelly; Sweitzer, Nevada; Jamelske, Eric M. (My University, 2019)
Although fruit and vegetable (FV) consumption lowers risks for many chronic diseases, children/adults tend under-consume FV. Research suggests that Supplemental Nutrition Assistance Program (SNAP) households purchase fewer healthy foods and more unhealthy foods compared to non-SNAP households. Thus, increasing purchases of healthy foods, especially FV, among SNAP households has become an important focus among practitioners, policymakers, and researchers. This study reports on a program that doubles SNAP benefits used at the farmers market up to $10/week. Using data collected from the farmers market we characterize program usage from 2014-18. We also report on survey results highlighting benefits of the program reported by SNAP households. Our results show that the market match program has significantly increased the number of SNAP shoppers using the farmers market and has also increased the frequency of trips to the farmers market. Survey responses show that significant percentages of SNAP farmers market shoppers report purchasing/eating more FV and say that it helps increase their budget. These results suggest that SNAP families are gaining access to healthier food 110 Poster Presentations: Social Sciences through the market match program. However, the use of SNAP benefits at the farmers market in 2018 represented less than 10% of SNAP households suggesting additional promotions are needed to increase usage which will require additional resources. This research has policy relevance as it helps us understand the impacts of a program designed to improve access to healthy foods for low income families.
Color poster with text, images, charts, photographs, and graphs.
Keywords: Low-income families; Food security; Farmers’ markets; Public welfare; Posters; Department of Economics